Evaluation of T memory cells in knee osteoarthritis patients - Rehab S. Mohamed; Alaa M. Hashim; Abdelhafeez M. Moshrif; Ali Sobhy (Al-Azhar Assiut Medical Journal)
Background and aim Knee osteoarthritis (OA) is a common chronic condition resulting in pain, fatigue, functional limitations, increased healthcare utilization, and high economic costs to society. Therefore, this study aims to assess the role of T memory cells in the pathogenesis of knee OA. Patients and methods This case–control study was carried out on 30 symptomatic patients with radiographic evidence of knee OA, who were attending Al-Azhar University Hospital, Assuit and 30 healthy volunteers. All the included patients were subjected to radiographic examination, Western Ontario and McMaster Universities score, Kellgren–Lawrence grade, and laboratory investigations (complete blood count–C-responsive protein–erythrocyte sedimentation rate) and assessment of T memory cells by flow cytometry. Results The mean CD3+CD4+CD8− T cells level, CD3+CD4+CD45Ro+ memory T cells level, CD3+CD8+CD4− T level, and CD3+CD8+CD45RO+ memory T was lower in OA cases (4.8±3.1) in comparison with controls. There was a significant moderated positive correlation between both grading scales and monocyte%, and between Kellgren–Lawrence grade and CD3+CD8+CD4− T cells (r=0.491, P=0.011) with an increase in disease severity, there was an increase in the CD3+CD8+CD4− T cells. Conclusion T memory cells have critical importance in the pathogenesis of knee OA. CD4+ T cells may serve a role in inducing inflammation in the early stages of OA, as well as being instrumental in causing inflammatory damage to the articular cartilage in the latter stages.